Between Faith and Finance: Can Religiosity and Islamic Financial Literacy Curb Impulsive Buying in Game Microtransactions? - Prasetya, Naufal Rizky; Nurafini, Fira (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
Ideally, as Muslims, Generation Z should be able to control their consumptive behavior in purchasing virtual game items through an understanding of religious values and Islamic financial literacy. However, in reality, impulsive behavior in game microtransactions is still prevalent among them. This study aims to analyze the influence of religiosity and Islamic financial literacy on impulsive buying among Muslim Generation Z in Surabaya. This article is categorized as field research with a quantitative approach. The methodology used is an associative quantitative method, which seeks to analyze the relationship between variables. The results of the study conclude that religiosity has a negative effect on impulsive buying, whereas Islamic financial literacy has a positive effect. This indicates that despite having a high understanding of Islamic financial principles, the weak application in daily life leads to continued consumptive behavior.